2021
DOI: 10.3389/fnmol.2020.618020
|View full text |Cite
|
Sign up to set email alerts
|

AAV Targeting of Glial Cell Types in the Central and Peripheral Nervous System and Relevance to Human Gene Therapy

Abstract: Different glial cell types are found throughout the central (CNS) and peripheral nervous system (PNS), where they have important functions. These cell types are also involved in nervous system pathology, playing roles in neurodegenerative disease and following trauma in the brain and spinal cord (astrocytes, microglia, oligodendrocytes), nerve degeneration and development of pain in peripheral nerves (Schwann cells, satellite cells), retinal diseases (Müller glia) and gut dysbiosis (enteric glia). These cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 235 publications
2
36
0
Order By: Relevance
“…Data on the detailed biology of HSV-1 infected neurons in the human TG will also be of benefit in the development of strategies to strengthen immune control of latent HSV-1 in ganglia. For example, it may be possible to improve intrinsic immunity of neurons and antiviral activities of SGC using vector delivered gene augmentation in a safe and cell type-dependent manner ( 197 , 198 ).…”
Section: Future Directions For Therapeutic Interventionmentioning
confidence: 99%
“…Data on the detailed biology of HSV-1 infected neurons in the human TG will also be of benefit in the development of strategies to strengthen immune control of latent HSV-1 in ganglia. For example, it may be possible to improve intrinsic immunity of neurons and antiviral activities of SGC using vector delivered gene augmentation in a safe and cell type-dependent manner ( 197 , 198 ).…”
Section: Future Directions For Therapeutic Interventionmentioning
confidence: 99%
“…AAV are considered optimal for human gene therapy as they are small and non-replicative, can transduce dividing and nondividing cells, are non-pathogenic in humans, and can determine long-lasting changes in gene expression. Importantly, AAV have been used to target several cell types, including microglia ( 24 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we explored the potential use of microglia engineered to express IL-15 upon infection with a recombinant adeno-associated virus serotype 2 (rAAV2) carrying IL-15 (rAAV2-IL-15), to simulate the effect of EE on glioma. AAV are considered safe for human gene therapy and have been successfully used to target several cell types within the central (CNS) and peripheral nervous systems (PNS), including neurons, oligodendrocytes, astrocytes, Müller glia, Schwann cells, and also microglia ( 24 ). We demonstrated that rAAV2-IL-15 microglia increase the viability of cocultured NK cells, without affecting their activation state in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Application of AAVs, specifically AAV8 and AAV9, provides variable results depending on experimental conditions, AAV production protocols, and region- and cell-specific characteristics in the injection area. Application of natural AAV serotypes for cell-specific transduction has obvious limitations that can be bypassed by generating synthetic “designer” AAV variants with specified, enhanced properties through rational engineering of AAV capsids or using a directed evolution approach [ 67 , 73 , 150 , 151 , 152 ]. Realizing these strategies for developing novel synthetic serotypes for astrocytic targeting has excellent potential for basic and translational neuroscience.…”
Section: Discussionmentioning
confidence: 99%